Changing Urban Ecology a Challenge for Coastal Urban Resilience: A Study on Muscat. (March 2020) - Nasiri, Noura Al; Al-Awadhi, Talal; Hereher, Mohamed; Ahsan, Reazul; AlRubkhi, AL Ghaliya
Rapid urbanisation has always been considered a determinant of the changing urban ecology, which encompasses vegetation, open spaces and vacant land to a compact urban area. Such changes of urban ecology expose coastal cities and make them vulnerable to natural disasters like flash floods and storm surges. This study uses the Compound Annual Growth Rate model and geospatial analysis to assess the changes to the urban ecology along the 43 km long coastline of Muscat, one of the fastest growing highly urbanized coastal capitals of the Arab world. The changes are calculated on 5 m and 10 m datums for three time periods (1990s, 2010s and 2017 onwards). The study finds that since the 2010s both the agricultural and low land have changed to a compact urban built-up area; highly dense vegetation and open spaces changed to scattered ornamental plantation and impervious areas. Such changes to the urban ecology along the coastline increase the vulnerability of Muscat to both sudden and slow onset of natural disasters. A critical literature analysis was also conducted to understand the changes to the urban ecology due to urbanization of global coastal cities in comparison to Muscat. With the quantitative data from the growth model and qualitative approach from critical literature analysis, this article finds that urban resilience for the Muscat coastline has been compromised due to changes in the urban ecology.